Study of a fuel electrode-supported solid oxide electrolysis cell prepared by aqueous co-tape casting - Liu, Chao (2021)
High temperature solid oxide electrolysis cells (SOECs) have the potential to efficiently and economically produce of hydrogen fuels. In this paper, large area fuel electrode-supported half cells with Zr0.92Y0.08O2-δ (YSZ) electrolyte and Ni/YSZ fuel electrode were fabricated by aqueous-based co-tape casting in conjunction with co-sintering, and the air electrode with La0.6Sr0.4Co0.2Fe0.8O3+δ/Ce0.9Gd0.1O2+δ (LSCF/CGO) was fabricated by screen printing. In solid oxide fuel cell (SOFC) mode, the maximum power density is 447 mWcm-2at 800 °C with humidified H2as the fuel and air as the oxidant. In solid oxide electrolysis cell (SOEC) mode, the hydrogen production rate of button cell is 222.2 ml h-1cm-2under an electrolysis voltage of 1.3 V with 70 vol.% steam.